Unveiling Smartphone Addiction Among Secondary School Students in an Emerging Country - Arifur Rahman; Tangina Akter; Nurun Nahar; Md. Mahbubur Rahman (Scientia Publica Media, 2026)
This study aims to investigate smartphone addiction among secondary school students in Bangladesh, along with its causes, effects, and potential preventive interventions within the socio-cultural context. The present study employed a mixed-methods approach. The Smartphone Addiction Scale Short Version (SAS-SV) was administered in eight schools from four districts, considering urban and rural schools. Then, students’ data were collected randomly from each school. After that, twelve students who scored top on that scale were selected for in-depth interviews, along with twelve parents and twelve class teachers, who were chosen purposively. In addition, an educationist and a psychologist were purposively selected for the interviews. This study found that the percentage of high, moderate, and low-risk students was 23%, 22.3%, and 54.8%, respectively. The prevalence of moderate and high risk of smartphone addiction is greater among male students (57.3% and 63%, respectively) than among female students (42.7% and 37%). Besides, urban students exhibited higher percentages in the moderate (56.2%) and high-risk (68.5%) categories compared to rural students, who had lower percentages (43.8% and 31.5%, respectively). This study finds some factors, such as personal, parental, social, academic, and resource-related factors, that contribute to smartphone addiction among secondary school students. Moreover, this study finds that smartphone addiction has a detrimental effect on students’ personal, social, and academic well-being. This study proposes several preventive measures, including enhancing self-esteem and determination, raising awareness among all relevant stakeholders, implementing effective parental mediation, providing teacher training and engaging them in anti-addiction activities, establishing rules and regulations, and maintaining ongoing monitoring and supervision.